Phylogeographic dynamics and molecular characteristics of Enterovirus 71 in China - Ma, Zi-Hui; Nawal Bahoussi, Amina; Tariq Shah, Pir; Guo, Yan-Yan; Dong, Li; Wu, Changxin; Xing, Li (Frontiers in Microbiology, 2023)
Enterovirus 71 (EV71) and coxsackievirus (CV-A16) are the major etiological agents of hand, foot and mouth disease (HFMD). This report reviewed the full-length genomic sequences of EV71 identified in different provinces of China between 1998 and 2019 (a total of 312) in addition to eight worldwide reference genomes to address the genomic evolution and genetic events. The main prevalent EV71 strians in China are C4 genotypes, co-circulating with a few A, B5, C1, and C2 subgenotypes. A new emerging subgenotype in China was identified and classified as B6 genotype. Phylogeographic analysis revealed multiple branches, where a Jiangsu strain 2006-52-9 (GenBank ID: KP266579.1) was linked to different subgenotypes through multiple long mutant branches, including the CV-A16 viruses through the A genotype. Furthermore, identification of 28 natural recombination events suggests that the emergence of new genotypes are associated with intratypic recombination involving EV71 strains and intertypic recombination between EV71 and CV-A16 strains. Compared with the structural proteins, the non-structural proteins of EV71 seem to be highly variable with the highest variable regions of peptidase C3 (3C protein), P2A, and the N-terminus of RNA-dependent RNA polymerase. This study updates the phylogenetic and phylogeographic information of EV71 and provides clues to the emergence of new genotypes of EV71 based on genetics.